A study on the effectiveness of programs and activities held by the Manila City Library system in the promotion of its library - Generao, Christian Arne B. (2008)
Public libraries, aside from schools, serve as the cornerstone of the education of the community in which these are situated. Apart from its collection, the extent of a public library's services such as its programs and activities must be taken into consideration not only to promote itself as an institution but also to meet the needs and expectations of its patrons towards quality service. It is for this reason that this study focused on the effectiveness of the programs and activities conducted by the Manila City Library System.